The Role of Endoscopic Ultrasound in Cystic Pancreatic Tumor Treatment - Moparty, Bhavani (Gastroenterol Hepatol (N Y), 2006)
Pancreatic cysts are being detected with increasing frequency. These lesions may be pseudocysts, serous cystadenomas, mucinous neoplasms, or other rare pancreatic malignancies. It is important to differentiate among the various cystic lesions in order to further guide management. We review the role of endoscopic ultrasound, fine needle aspiration including cytology, and tumor markers in the evaluation of these cystic tumors. We also discuss emerging concepts in the management of cystic pancreatic tumors.